ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI PADA PT. DWI JAYA MAJU PERKASA PALEMBANG - Rizal Effendi (JURNAL KOMPETITIF, 2014)
The selling price of goods is determined before production orders done, the company will calculate the cost elements contained in the production are estimated. This assessment is based on the standard cost (standard cost) which has been determined in advance by the company. If the state of the economy is assumed to be stable in which prices are generally relatively constant then the estimated production cost can approach the actual cost of production. Ã‚Â Keywords: Standard cost, cost of production